Pengaruh Kecerdasan Emosional dan Spiritual terhadap Pemahaman Akuntansi Keuangan dengan Motivasi Belajar sebagai Intervening - Bernica, Femi; Fachruzzaman, Fachruzzaman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research investigates how emotional and spiritual intelligences affect students’ grasp of financial accounting, with learning motivation serving as an intervening factor. Employing a quantitative design and analyzed through Partial Least Squares–based Structural Equation Modeling (SEM-PLS), data were gathered via questionnaires from 193 accounting undergraduates at the Faculty of Economics and Business, University of Bengkulu (semester 5 or above) who have completed Financial Accounting I, II, and III, selected through purposive sampling. Findings indicate that emotional intelligence exerts a positive, significant direct impact on accounting comprehension, and spiritual intelligence likewise shows a positive, significant influence. However, emotional intelligence does not significantly predict learning motivation, whereas spiritual intelligence strongly drives it. Moreover, learning motivation mediates only the link between spiritual intelligence and accounting understanding, not the connection involving emotional intelligence. These results underscore the value of embedding spiritual dimensions into the curriculum to bolster students’ intrinsic drive and mastery in financial accounting.